The Role of Digital Transformation in Optimizing Market Reach and Data Management for SMEs - Pratiwi, Ratih; Maulidya, Sapta Yulinar (Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 2025)
Rapid technological developments force Micro, Small, and Medium Enterprises (MSMEs) to adapt through digitalization, both in business operations and data management. This study aims to analyze the challenges and opportunities in the MSME digitalization process and evaluate their readiness to implement personal data protection regulations under Law No. 27 of 2022. The study employs a qualitative approach with literature review methods from various academic and practical sources related to MSME digitalization and data protection. The findings reveal that although digitalization offers numerous benefits, most MSMEs in Indonesia face significant challenges, such as limited digital skills and high technology implementation costs. Moreover, MSMEs’ awareness and understanding of personal data protection regulations are still low, posing potential legal risks in the future. Strategic measures are needed, including digital skill enhancement, financial support, and education on data management, to support MSMEs in achieving successful digital transformation and improving their competitiveness.